Potential Roles of Enterochromaffin Cells in Early Life Stress-Induced Irritable Bowel Syndrome - Tao, Enfu; Zhu, Zhenya; Hu, Chenmin; Long, Gao; Chen, Bo; Guo, Rui; Fang, Marong; Jiang, Mizu (Frontiers in Cellular Neuroscience, 2022)
Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders, also known as disorders of the gut-brain interaction; however, the pathophysiology of IBS remains unclear. Early life stress (ELS) is one of the most common risk factors for IBS development. However, the molecular mechanisms by which ELS induces IBS remain unclear. Enterochromaffin cells (ECs), as a prime source of peripheral serotonin (5-HT), play a pivotal role in intestinal motility, secretion, proinflammatory and anti-inflammatory effects, and visceral sensation. ECs can sense various stimuli and microbiota metabolites such as short-chain fatty acids (SCFAs) and secondary bile acids. ECs can sense the luminal environment and transmit signals to the brain via exogenous vagal and spinal nerve afferents. Increasing evidence suggests that an ECs-5-HT signaling imbalance plays a crucial role in the pathogenesis of ELS-induced IBS. A recent study using a maternal separation (MS) animal model mimicking ELS showed that MS induced expansion of intestinal stem cells and their differentiation toward secretory lineages, including ECs, leading to ECs hyperplasia, increased 5-HT production, and visceral hyperalgesia. This suggests that ELS-induced IBS may be associated with increased ECs-5-HT signaling. Furthermore, ECs are closely related to corticotropin-releasing hormone, mast cells, neuron growth factor, bile acids, and SCFAs, all of which contribute to the pathogenesis of IBS. Collectively, ECs may play a role in the pathogenesis of ELS-induced IBS. Therefore, this review summarizes the physiological function of ECs and focuses on their potential role in the pathogenesis of IBS based on clinical and pre-clinical evidence.